OCCURRENCE OF FOLIVOROUS INSECT ON MANGROVE SEEDLINGS IN PANTAI PANJANG NATURE RECREATION PARK - Farma, Albert; Susanti, Amelia Dwi; Faramudita, (Jurnal Silva Samalas, 2026)
Mangrove seedling are vulnerable to pest disturbances that can affect stand health and regeneration success. This study aimed to identify leaf-eating insect species and analyze pest attack incidence and damage intensity on Rhizophora apiculata and Bruguiera gymnorhiza in Pantai Panjang Nature Tourism Park. Observations were conducted over four months (March–June) using direct field observation methods on established sampling plots. Four leaf-eating insect pest species were recorded: Attacus atlas (Atlas Moth), Metisa plana and Mahasena corbetti (Bagworms), and Oxya japonica (Migratory Grasshopper). Pest attack incidence on R. apiculata was consistently higher than on B. gymnorhiza throughout the observation period, with the highest values recorded in June. Damage intensity on both species ranged from 15–23%, peaking in April–May, and was classified as very light and light on leaf damage scoring criteria. These findings are expected to serve as a reference for developing appropriate pest monitoring and management strategies to support the sustainability of mangrove ecosystems in Pantai Panjang Nature Tourism Park.